Virtual museums : Captured reality and 3D modeling - Loaiza Carvajal, Daniel Alejandro (2020)
Virtual spaces for the dissemination of cultural heritage and virtual experimentation were developed combining 3D image acquisition techniques like digital photogrammetry (captured reality) and computer 3D modeling. This is a novelty in peripheral countries, particularly in Latin-America, since there is almost no development of this kind of virtual museums in the region. Two virtual scenes are presented in the frame of a digitization project of the collections of Argentine museums. On one hand, a virtual museum named Virtual Collections was created. It exhibits, in a computer generated environment, the collections of the participating museums in the aforementioned project, digitized by 3D photogrammetry. On the other hand, a virtual tour that recreates a retrospective exhibition was also built as an interactive recording for documentation of the event. In both cases 3D modeling and texturing techniques were used, achieving realistic results. Two instances of immersion are available for the visualization and interaction with both virtual environments: screen, keyboard and mouse (Desktop VR) and HTC Vive (VR visualization headset).